Utility of Linearly Amplified RNA for RT-PCR Detection of Chromosomal Translocations : Validation Using the t(2;5)(p23;q35) NPM-ALK Chromosomal Translocation - Schumacher, Jonathan A. (American Society for Investigative Pathology, 2004)
The requirement for sufficient quantities of starting RNA has limited the ability to evaluate multiple transcripts using reverse transcriptase-polymerase chain reaction (RT-PCR). In this study, we demonstrate the utility of linear RNA amplification for RT-PCR analysis of multiple gene transcripts including a chromosomal translocation, using the t(2;5)(p23;q35) as a model. RNA from the t(2;5)-positive cell line, SU-DHL-1, and the t(2;5)-negative cell line, HUT-78, was extracted and exposed to two rounds of linear amplification. RT-PCR using cDNA from the resultant amplified (a) RNA and total RNA resulted in the 177 bp NPM-ALK fusion gene product from the SU-DHL-1 cell line, but not from aRNA or total RNA from the HUT-78 cell line. DNA sequencing of the RT-PCR products from total and aRNA of SU-DHL-1 cells demonstrated identical sequences corresponding to the NPM-ALK fusion gene. Evaluation of 25 snap-frozen tissue samples, including eight NPM-ALK-positive ALCLs demonstrated 100% concordance of t(2;5) detection between cDNA from total RNA and that from aRNA. Our results show that linear amplification of RNA can enhance starting RNA greater than 200-fold and can be used for rapid and specific detection of multiplex gene expression from a variety of sources. This method can generate a renewable archive of representative cDNA, which can be used for retrospective screening of stored samples as well as positive controls for the clinical molecular diagnostic laboratory.